Profil Pelajar Pancasila dari Perspektif Persatuan Guru Nahdlatul Ulama (Pergunu) Kabupaten Kediri - Yani, Muhammad Turhan; Rosyanafi, Rofik Jalal; Hazin, Mufarrihul; Cahyanto, Bagus; Nuraini, Febritesna (Universitas Negeri Surabaya, 2024)
This research aims to elucidate a comprehensive overview of Pancasila students as a strategic step in shaping the national character, particularly within the context of the Nahdlatul Ulama Teachers Union (Pergunu) in Kediri Regency. The employed method in this study is the literature review method, involving a series of activities related to the collection, reading, recording, and processing of data from various literary sources. Findings from this research highlight that the profile of Pancasila students plays a significant role in supporting national educational goals and advancing character strengthening programs. This profile encompasses essential characteristics and competencies for Indonesian students, both in the formal learning context and in interactions with society. Through the application of six dimensions of the Pancasila student profile—faith and piety to God Almighty, global diversity, self-reliance, mutual cooperation, critical thinking, and creativity—it is anticipated that the Indonesian society can become individuals who are intelligent, character-driven, and capable of facing 21st-century challenges. This is also expected to consistently instill Pancasila values, in accordance with our national philosophy, ultimately realizing a prosperous and dignified life for the nation as mandated by the 1945 Constitution. The development strategy of the Pancasila student profile is implemented through integration into formal education activities, such as intracurricular, extracurricular, and cocurricular activities, organized in the form of Pancasila student profile strengthening projects. Through the implementation of this policy, it is hoped to cultivate excellent character in the Indonesian student generation, enabling them to compete globally.